Pelatihan Pembuatan Silase Fermentasi Batang Pisang sebagai Subtitusi Penggunaan Hijauan di Kelompok Tani Mekar Jaya Kampung Pinang, Sebatang Timur Kecamatan Siak, Provinsi Riau - Zulia Jati, Putri; Novita, Maulina; Zaki, M; Aswara, Dana; Dimas Setiawan, Bagus (Journal of Social and Community Service, 2022)
The decrease in the area of ​​agricultural land has an impact on the availability of forage products that have been used by the community as animal feed. The lack of forage products encourages people to use agricultural waste as animal feed. Agricultural waste has lower quality compared to conventional feed. In an effort to improve and provide for the nutrients that are lacking in feed, it is necessary to provide additional supplements so that livestock nutrition can be fulfilled. One technology that can be used is the Batang Pisang silage dryer. Is a substitute feed for ruminants to increase the digestibility of low-quality feed, overcome nutritional deficiencies and increase livestock appetite. Thus avoidance of feeding can increase livestock productivity. Fast food feed training has been carried out for cattle breeders who are domiciled in the Mekar Jaya Farmer Group in Kampung Pinang, Sebatang Timur, Siak District, Riau Province. Cattle farms that are participating in the activity respond well to the implementation of this feed cultivation. Through this training, it is hoped that the feed community will be able to cut banana stems on their own to develop a cattle farming business.